The association between arterial stiffness and socioeconomic status: a cross-sectional study using estimated pulse wave velocity - Hack-Lyoung Kim; Soonil Kwon; Hyun Sung Joh; Woo-Hyun Lim; Jae-Bin Seo; Sang-Hyun Kim; Joo-Hee Zo; Myung-A Kim (BMC, 2024)
Abstract Background The impact of socioeconomic status (SES) on arterial stiffness remains unclear. This study aimed to explore the association between both personal and household income, as well as education level, and estimated pulse wave velocity (ePWV). Methods A total of 13,539 participants (mean age 52.9 ± 16.7 years; 57.1% women) from the Korean National Health and Nutrition Survey database were analyzed. For SES variables, information on personal and household income and education level was collected using standardized questionnaires. Results The ePWV did not show significant differences across groups categorized by individual income levels (P = 0.183). However, there was a noticeable trend of decreasing ePWV with increasing household income levels (P < 0.001). Additionally, ePWV demonstrated a significant negative correlation with higher education levels, indicating that ePWV decreased in groups with higher educational attainment (P < 0.001). In multiple linear regression analyses, both household income (β = -0.055; P < 0.001) and education level (β = -0.076; P < 0.001) were negatively associated with ePWV, even after adjusting for potential confounders. Conclusions Lower household income and lower education levels were associated with higher ePWV, providing further evidence of the influence of SES on arterial stiffness. Graphical abstract